BET proteins in abnormal metabolism, inflammation, and the breast cancer microenvironment. Issue 2 (1st March 2018) - Andrieu, Guillaume P.; Shafran, Jordan S.; Deeney, Jude T.; Bharadwaj, Kishan R.; Rangarajan, Annapoorni; Denis, Gerald V.
Abstract: Obesity and its associated pathology Type 2 diabetes are two chronic metabolic and inflammatory diseases that promote breast cancer progression, metastasis, and poor outcomes. Emerging critical opinion considers unresolved inflammation and abnormal metabolism separately from obesity; settings where they do not co‐occur can inform disease mechanism. In breast cancer, the tumor microenvironment is often infiltrated with T effector and T regulatory cells programmed by metabolic signaling. The pathways by which tumor cells evade immune surveillance, immune therapies, and take advantage of antitumor immunity are poorly understood, but likely depend on metabolic inflammation in the microenvironment. Immune functions are abnormal in metabolic disease, and lessons learned from preclinical studies in lean and metabolically normal environments may not translate to patients with obesity and metabolic disease. This problem is made more urgent by the rising incidence of breast cancer among women who are not obese but who have metabolic disease and associated inflammation, a phenotype common in Asia. The somatic BET proteins, comprising BRD2, BRD3, and BRD4, are new critical regulators of metabolism, coactivate transcription of genes that encode proinflammatory cytokines in immune cell subsets infiltrating the microenvironment, and could be important targets in breast cancer immunotherapy. These transcriptional coregulators are well known to regulate tumor cell progression, but only recently identified as critical for metabolism, metastasis, and expression of immune checkpoint molecules. We consider interrelationships among metabolism, inflammation, and breast cancer aggressiveness relevant to the emerging threat of breast cancer among women with metabolic disease, but without obesity. Abstract : Type 2 diabetes is an understudied contributor to progression of breast cancer; disease‐associated chronic inflammation by BET proteins is a dangerous modifier of tumor microenvironments.